Response of improved Brachiaria (Urochloa) grass cultivars to foliar diseases and their agronomic performances in Rwanda - Uzayisenga, Bellancile; Mutimura, Mupenzi; Muthomi, J.W.; Mwang’ombe, A.W.; Ghimire, Sita R. (National Inquiry Services Center, 2021)
Diseases have emerged as one of the major challenges of Brachiaria production in Africa. Nine Brachiaria cultivars were evaluated for leaf rust, leaf spot and leaf blight diseases and agronomic performances in two agro-ecological zones of Rwanda. The relationships between agronomic traits and area under diseases progress curve (AUDPC) were determined using Pearson correlation analysis. Cultivars differed significantly (p ≤ 0.05) for their response to these three diseases. Basilisk, Marandu, MG4, and Xaraes exhibited moderately resistant to resistant response to all three diseases, but Cayman and Cobra were susceptible to leaf rust. Site × cultivar × harvest interaction was significant for diseases and agronomic parameters (p ≤ 0.05). Cultivars also differed significantly for biomass production and dry matter content (p ≤ 0.05). The highest biomass producers were Marandu and Xaraes, and Cayman, Cobra and Piata had highest dry matter content. The AUDPC for leaf rust and leaf spot had negative and significant correlation with biomass yield. Our study concludes a satisfactory level of resistance in Basilisk, Marandu, MG4 and Xaraes to all three foliar disease in Rwanda. We recommend routine surveys for emerging and re-emerging Brachiaria diseases and studies to develop effective management measures against Brachiaria diseases.